On Brachysira follis (Ehrenberg) Cleve and Navicula trochus Ehrenberg (Bacillariophyceae) - Kusber, Wolf-Henning; van De Vijver, Bart (Phytotaxa, 2025)
During a recent revision of the genus Brachysira in Europe, Navicula follis, the basionym of Brachysira follis, was excluded. Studies of Ehrenberg’s original materials and publications revealed unexpected inconsistencies in Ehrenberg’s publications. Analysis of the original materials of Navicula trochus and Navicula follis ascertained that both species are conspecific.